Eksperimen Estimasi Biaya Proyek Perangkat Lunak Menggunakan Metode Function Point Analysis (FPA) - Hendrawan, Hendrawan; Jusia, Pareza Alam; Rasywir, Errissya; Pratama, Yovi (STMIK Budi Darma, 2019)
In building software, it should start with project planning. This activity is initialized with estimation activity. When estimation is done, it is necessary to make predictions in the future and handle the uncertainty that will be passed in running a software project. There are several options in project estimation. However, in this study, we used the most common and familiar technique to be tested on project data that had been running in the field. From the results of experiments conducted in the study on 20 (twenty) data software development projects in one of the software houses in Jambi city using the Function Point Analysis (FPA) method, the results of the calculation of the RMSE (root mean squared error) of Rp 1,073,001, - and an error value of 0.25. This means that it can be concluded that the difference in RMSE from the real price comparison transacted in the field with the price estimated using the Function Point Analysis (FPA) method is equal to the value mentioned above, which value includes a value with a fairly small gap. As well, the error value produced is also quite small at 0.25.